Pemanfaatan Media Sosial Instagram Dalam Meningkatkan Hasil Penjualan Angkringan Pojok Sate Taichan Jl. Letjend Suprapto Kota Bengkulu - Suharmi Suharmi; Melda Ratnawati; Ayudho Selviani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to explore how Pojok Sate Taichan business on Jl. Letjend Suprapto, Bengkulu City utilizes Instagram social media to enhance sales performance. This qualitative study employs an inductive thinking approach to understand the reality of the subject matter. The subjects of this study are the operators of Pojok Sate Taichan on Jl. Letjend Suprapto, Bengkulu City. The object of the study is the utilization of social media by the operators of Pojok Sate Taichan on Jl. Letjend Suprapto, Bengkulu City. The findings reveal that Pojok Sate Taichan in Bengkulu effectively utilizes Instagram's Story and Reel features, resulting in a significant increase in daily sales by 39-50% and daily revenue by 15-20%. A comparison before and after using social media indicates a perceived increase in sales results by up to 133% and revenue by approximately 80% for the business operators. Therefore, the effective integration of Instagram social media by Pojok Sate Taichan on Jl. Letjend Suprapto, Bengkulu City has positively impacted the growth of SMEs, such as increased sales, revenue, and opportunities for investment and further expansion.